Molecular Dynamic Investigation of Graphene Oxide Presence and Three Experimental Distribution Methods in Reinforced Epoxy-Based Nanocomposites - Mohsen Ghiasvand; Hamid Fazeli; Jafar Eskandari Jam; Abass Kebritchi (Mechanics of Advanced Composite Structures)
Because of the relatively high specific mechanical properties of LY556 epoxy resin, is often used as an important matrix for structural composites in high-performance applications. In the current study, an atomistic simulation based on molecular dynamics was performed to characterize the mechanical properties of LY556 epoxy (EP) nanocomposites reinforced with graphene oxide (GO) nanoparticles. The stiffness matrix and elastic properties such as Young’s modulus, shear modulus, and Poisson’s ratio for the pure EP and EP/GO nanocomposites were estimated using the constant-strain method. Three distribution methods including ultrasonic with a probe, mechanical mixing with an ultrasonic cleaner, and a high-shear turbo mixer with an ultrasonic cleaner were employed. The role of the distribution method on the tensile behavior of epoxy reinforced with varying percentages of GO nanoparticles (0.3 and 0.5 wt. %) was investigated. In addition, X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) were employed to investigate the quality of GO distribution in nanocomposites. In the M3 method (the optimal method) the tensile strength of the EP/GO nanocomposite was increased about 15% (76 MPa) at 0.3 wt% and 22% (80 MPa) at 0.5 wt%. Moreover, the toughness of the EP/GO nanocomposite was improved by around 34% (1.37 J.m-3) and 50% (1.53 J.m-3) at 0.3 and 0.5 wt% respectively.